Silent victims: why do battered husbands in Malaysia not come out of the closet? / Kitson Foong - Kitson, Foong (2008)
Domestic violence is a disturbing and distressing grim reality in many households. Of late, increasing public concern and statistical research in the field of domestic violence in Malaysia has focused exclusively on wife abuse with no mention of the male victim of female spousal aggression. Whilst husband battering is known to occur virtually no studies empirical or otherwise have been conducted in this country to probe into this controversial topic. This research paper is an attempt by the writer firstly to verify via a series of intimate interviews whether husband battering does in fact occur in Malaysian households. The writer explores the profile of a husband batterer in an attempt to gain further insight into the motivations of the female aggressor. More importantly the writer seeks to examine the rationale behind the plethora of reasons why the victim husband ch•Jose~ to remain silent and not come out of the closet. The decision to stay on is often, in itself, a heart-wrenching one. The male victim of female spousal aggression is oftentimes stigmatized by his family, friends and community and rarely offered any comfort or shelter let alone a helping hand. Deeply ingrained patriarchal attitudes within the agencies involved in the dispensation of criminal justice have exacerbated the problem. Rather than being providers of support and protectors of such victims, those involved in the criminal justice system have indirectly turned them away. The civil justice system vide the Family Court has not assisted much either. It is hope that this paper will stir further research into this area in the future. Whilst not intended as an all encompassing research, this research hopefully stirs the reader to acknowledge the presence of certain discriminations that may be deeply buried at the back of the reader's minds with a prayer that after being put to a better understanding of the plight of a battered husband these prejudices may be permanently erased.